Development Strategy for Health Behavior of the Elderly - Hantrakul, Pagapan; Saengthong, Suchat; Vongkamjan, Supawan (Mediterranean Journal of Social Sciences, 2013)
The research objectives were 1) to examine the health problems of elderly people who resided in urban community around theDevelopment Strategy Practice Centre in Nakhon Sawan Municipality, 2) to construct development strategy of strategies forenhancing health behaviour of the elderly people, and 3) to experiment the strategies with the target group of elderly people.The research design was mixed methods of quantitative and qualitative approaches. The population comprises 897 elderlypeoples who live around the Centre. The purposive sampling was used for sample selection of 30 elderly who were voluntarilyassigned as an experimental group. The research tools used are a structured in-depth interview, a self-administeredquestionnaire, participation observation, and a test of knowledge, skills and attitudes of health behavior. The findings revealedthat the elderly peoples suffered from the following problems: non-exercise, malnutrition, anxiety, and illness resulting fromafore mentioned. Therefore, the constructed development strategy for solving the health behavior problems of the elderlypeople based on food, drinking water, fresh air, emotion, Thai massage, and music (singing, listening, and playing). Theinstrument for data collection was a Likert-scale questionnaire. The finding revealed that 30 elderly peoples before training andat the twelfth week about weight, body index, upper blood pressure, lower blood pressure, heart rate, waistline, and bloodsugar level were different with statistical significance at .001.